2016
DOI: 10.1002/14651858.cd005001.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for women receiving adjuvant therapy for breast cancer

Abstract: Background A huge clinical research database on adjuvant cancer treatment has verified improvements in breast cancer outcomes such as recurrence and mortality rates. On the other hand, adjuvant and neoadjuvant therapy with chemotherapy and radiotherapy impacts on quality of life due to substantial short-and long-term side effects. A number of studies have evaluated the effect of exercise interventions on those side effects. This is an updated version of the original Cochrane review published in 2006. The origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
209
0
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(254 citation statements)
references
References 172 publications
19
209
0
26
Order By: Relevance
“…For the group of survivors in need of clinical care, it is critical to facilitate timely referrals to a multidisciplinary team of providers from cancer rehabilitation, palliative care, psychosocial care, exercise, nutrition, smoking cessation services, and hospice care when survivors approach the end of life. Cancer rehabilitation, palliative care, and psychosocial care interventions help manage symptoms and improve functioning and quality of life . Cancer rehabilitation interventions can help survivors maintain employment, contributing to better financial outcomes.…”
Section: Priority 2: Facilitate Personalized Tailored Care Informatimentioning
confidence: 99%
“…For the group of survivors in need of clinical care, it is critical to facilitate timely referrals to a multidisciplinary team of providers from cancer rehabilitation, palliative care, psychosocial care, exercise, nutrition, smoking cessation services, and hospice care when survivors approach the end of life. Cancer rehabilitation, palliative care, and psychosocial care interventions help manage symptoms and improve functioning and quality of life . Cancer rehabilitation interventions can help survivors maintain employment, contributing to better financial outcomes.…”
Section: Priority 2: Facilitate Personalized Tailored Care Informatimentioning
confidence: 99%
“…A large body of evidence has shown that, in healthy individuals, skeletal muscle adaptation to exercise training includes improvements in muscle strength, fiber area (13), markers of mitochondrial content and function, and capillarization (14). In patients with breast cancer, physical exercise counteracts the loss of muscle strength experienced after treatment (15). One training modality that induces significant muscle adaptation and health benefits in a time-efficient manner is high-intensity interval training (HIIT) (16), which has been trialed safely in patients with breast cancer (17), including in the current trial during chemotherapy (18).…”
mentioning
confidence: 99%
“…Despite the increasing number of studies showing the ability of exercise training to improve or maintain muscle strength and cardiorespiratory fitness in patients with cancer during chemotherapy (15), only 2 randomized, controlled exercise trials including resistance training (RT) for patients with prostate (19) and germ cell cancer (20,21) have investigated the molecular adaptations expected to occur with exercise training. Molecular musculoskeletal responses, including mitochondrial markers to exercise training in patients with breast cancer and adaptations to different exercise modalities during chemotherapy, have not been studied.…”
mentioning
confidence: 99%
“…Research has indicated that individual treatments delivered by rehabilitation professionals can reduce impairments or functional limitations of cancer survivors . For example, meta‐analyses or systematic reviews support the use of exercise to reduce fatigue and to improve physical fitness, physical and emotional function, and quality of life; education to manage pain and fatigue; nonpharmacological interventions or neuropsychological interventions to improve cognitive functioning; group‐based self‐management programs to improve physical functioning; massage therapy to improve pain, fatigue, and anxiety; and manual lymphatic drainage to manage lymphedema …”
Section: Introductionmentioning
confidence: 99%